Design & development on a myofibrillar force measurement system - Judohandoko, Kevin (2015)
Researches on how to prevent and how to treat cardiomyopathy; a disease that attacks human heart, have become a popular research topic. Many researches have been done to reveal the way to find the cure or the best way to prevent it to happen again. One of the researches studies the contractile properties of a single myofibril cell; a very tiny cell in human heart, by measuring the force it produces. Through which, it is desirable to understand more about the disease and find the cure. A myofibrillar force measurement system is used to study the contractile properties of the myofibril through measuring its forces. Thus, myofibrillar force measurement system is built from scratch since the myofbirillar force measurement system is not available in market. The focus in this project is to design and fabricate several customized components that are required to make the myofibril force measurement system, starting from the experimental chamber, customized bracket, customized connector, solution from controller, supporting mechanisms, and so on. Different possible designs are taken into consideration to have the best result possible. Thus, most of the designs are based on iterative design method which is based on theories and other existing design. The most important criteria to fulfill is that every component should eliminate every single possible noise from the system because the system deals with a tiny cell in a scale of micrometer. Subsequently, after all components are designed and fabricated, the author will assemble and put everything as one compact unit so it will ease the experiment process later on.